Spatial regression analysis for discovering quality living index (QLI) in Asia - Sumardi, Devina Gilar Fitri Ayu; Purwaningsih, Tuti (Association for Scientific Computing Electrical and Engineering, 2018)
The quality of life that is synonymous with welfare lately much discussed. Survival or quality of life is an important issue in the economy and political knowledge. Quality of life describes the achievement of an ideal human life or in accordance with the desired. The quality of life index (IKH) provides a comprehensive ranking of the quality of life of a society in a country around the world. According to katadata news and research in 2016, the quality of life in 5 Southeast Asian countries is ranked lowest. The research finds that there are regional imbalances based on the indices of quality of life in 2018. Therefore, countries in Southeast Asia need to be genjotic in all areas to boost contributions to the quality of life in the country, as Dominic Volek, Southeast Asia chief in Henley & Partners Singapore. In this study we use the data from numbeo.com to see the value of quality indices in Asia in 2018 with various supporting indicators such as purchasing power index, security index, health care index, cost of living index, property price to income ratio, time index travel traffic, pollution index, and climate index. Where this study aims to determine how much influence the indicators that have been determined to calculate the CPI, knowing the best spatial regression model that can be used and determine whether there is asi gap in the region of Asia. The results of this study hope can be useful information for the community and a reference to make policy by the state officials in the field, but it can be a research material that can be developed again to see the difference and development of quality of life index in each country in Asia next year.